PENJAMINAN MUTU PENDIDIKAN PADA PERGURUAN TINGGI DI JAWA TIMUR - admin admin; Sri Uchtiawati (Universitas Muhammadiyah Gresik, 2012)
In order to lead the worldwide human resources rivalry, Education in Indonesia should be able to increase its quality through Q A. The study focuses on efforts to prepare the implementation of Q A through accreditation and internal Quality Assurance because quality is a needed by education society. Therefore, in order to avoid fake value (just a “symbol” quality), education organizer needs comprehensive preparation for the true quality. Internal quality assurance implemented by the observed universities is to determine models suited with the condition of each setting so that they have different ways of implementation. The main goal of the internal quality assurance is to guarantee the quality of the higher education management by optimizing efforts to achieve quality standard. The implementation of this internal quality assurance usually relates to the visions and missions of theuniversity.